CCR7 Regulates Cell Migration and Invasion through JAK2/STAT3 in Metastatic Squamous Cell Carcinoma of the Head and Neck. (27th October 2014) - Liu, Fa-Yu; Safdar, Jawad; Li, Zhen-Ning; Fang, Qi-Gen; Zhang, Xu; Xu, Zhong-Fei; Sun, Chang-Fu
Abstract : Squamous cell carcinoma of the head and neck (SCCHN) frequently involves metastasis at diagnosis. Our previous research has demonstrated that CCR7 plays a key role in regulating SCCHN metastasis, and this process involves several molecules, such as PI3K/cdc42, pyk2, and Src. In this study, the goals are to identify whether JAK2/STAT3 also participates in CCR7's signal network, its relationship with other signal pathways, and its role in SCCHN cell invasion and migration. The results showed that stimulation of CCL19 could induce JAK2/STAT3 phosphorylation, which can be blocked by Src and pyk2 inhibitors. After activation, STAT3 was able to promote low expression of E-cadherin and had no effect on vimentin. This JAk2/STAT3 pathway not only mediated CCR7-induced cell migration but also mediated invasion speed. The immunohistochemistry results also showed that the phosphorylation of STAT3 was correlated with CCR7 expression in SCCHN, and CCR7 and STAT3 phosphorylation were all associated with lymph node metastasis. In conclusion, JAk2/STAT3 plays a key role in CCR7 regulating SCCHN metastasis.